2005
DOI: 10.1111/j.1440-1819.2005.01385.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aromatherapy massage on mild depression: A pilot study

Abstract: Japan. Detailed explanations of the project were given to each patient and all patients signed informed consent forms prior to participating.This study was carried out in five patients aged 31-59 years, with Diagnostic and Statistical Manual-IV classification of 296.21 Major Depressive Disiorder, Single Episode, Mild (not including psychotic features). One of these patients was male. None of the patients used antidepressants or received psychotherapy. Each received a 30-min aromatherapy massage using essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…Many studies suggested different treatment modalities for the management of anxiety and depression, and the equilibration of physiologic parameters, but an interest in the use of complementary and alternative therapies among older patients with heart diseases is increasing (Sibbritt, Davidson, DiGiacomo, Newton, & Adams, ). Various studies have confirmed the efficacy of nonpharmacological measures such as aromatherapy massage for relieving psychological symptoms in different groups of patients(Cooke & Ernst, ; Kuriyama et al, ; Okamoto et al, ), but immediate consequences and benefits of this therapy on the levels of anxiety and depression are still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies suggested different treatment modalities for the management of anxiety and depression, and the equilibration of physiologic parameters, but an interest in the use of complementary and alternative therapies among older patients with heart diseases is increasing (Sibbritt, Davidson, DiGiacomo, Newton, & Adams, ). Various studies have confirmed the efficacy of nonpharmacological measures such as aromatherapy massage for relieving psychological symptoms in different groups of patients(Cooke & Ernst, ; Kuriyama et al, ; Okamoto et al, ), but immediate consequences and benefits of this therapy on the levels of anxiety and depression are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…older patients with heart diseases is increasing (Sibbritt, Davidson, DiGiacomo, Newton, & Adams, 2015). Various studies have confirmed the efficacy of nonpharmacological measures such as aromatherapy massage for relieving psychological symptoms in different groups of patients (Cooke & Ernst, 2000;Kuriyama et al, 2005;Okamoto et al, 2005), but immediate consequences and benefits of this therapy on the levels of anxiety and depression are still unknown.…”
Section: Physiologic Parametersmentioning
confidence: 99%
“…Similarly, an open, semi-comparative trial with 12 breast cancer patients showed that anxiety, as measured by the State-Trait Anxiety Inventory (STAI), was significantly reduced after a 30-minute aroma body massage by skilled therapists [11]. Moreover, aroma massages twice a week for 4 weeks improved prefrontal cortex dysfunction and mild depression in 5 patients with depression [12]. These findings indicated that aroma massage is associated with a more relaxed mental condition as well as decreased BP and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…9 Aromatherapy massage using C. sinensis oil every week for 4 weeks improves depressive states in patients by increasing blood flow to the prefrontal cortex. 10 Stress-relieving properties could also be attributed to C. sinensis oil, measuring the saliva cortisol concentration. 11 An investigation at the Middlesex Hospital in London showed that foot massage with the essential oil from the flowers of C. aurantium (Neroli oil) positively affects the psychological state of patients.…”
Section: Introductionmentioning
confidence: 99%